Three Gay Tales from Grimm - Grimm, Jacob, 1785-1863 (Book collections on Project MUSE., 2008)
Bound by a common thread?a serene foolishness cropping up in many a character and absurd situation?the three charming tales in this long unavailable book are not as well-known as they deserve to be. Wanda Gág?s interpretations of?The Clever Wife? and?The Three Feathers? are exceptionally funny, while?Goose Hans? is particularly hard to find in Grimm collections. Gág?s uniquely American translations and her equally enchanting illustrations will provide sheer delight for the young and old.